2017
DOI: 10.1186/s41065-017-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk between the CACNA1I gene and schizophrenia in Chinese Uygur population

Abstract: BackgroundSchizophrenia (SCZ) is a common mental disorder with high heritability, and genetic factors play a major role in the pathogenesis. Recent researches indicated that the CACNA1I involved in calcium channels probably affect the potential pathogenesis of SCZ.ResultsIn this study, we attempted to investigate whether the CACNA1I gene contributes the risk to SCZ in the Uighur Chinese population, and performed a case-control study involving 985 patient samples and 1218 normal controls to analyze nine SNPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The intronic SNP rs3788567 was identified with very high significance in an Ashkenazi Jewish population [176]. In a study of an Uyghur Chinese population that comprised 985 patients and 1218 neurotypical controls, six SNPs within CACNA1I were significantly associated with SCZ (rs132575, rs136805, rs713860, rs738168, rs5757760, rs575087) [265]. Furthermore, rs4522708, rs3788568, rs5750862 were significantly associated with SCZ in a Han Chinese population [266,267].…”
Section: Genetic Associations Between Cav Genes and Psychiatric DImentioning
confidence: 99%
“…The intronic SNP rs3788567 was identified with very high significance in an Ashkenazi Jewish population [176]. In a study of an Uyghur Chinese population that comprised 985 patients and 1218 neurotypical controls, six SNPs within CACNA1I were significantly associated with SCZ (rs132575, rs136805, rs713860, rs738168, rs5757760, rs575087) [265]. Furthermore, rs4522708, rs3788568, rs5750862 were significantly associated with SCZ in a Han Chinese population [266,267].…”
Section: Genetic Associations Between Cav Genes and Psychiatric DImentioning
confidence: 99%
“…3 ). However, rs4522708 is not linked with other significant SNPs reported in previous study [ 30 ]. These LD analysis results suggested that several independent genetic variants in CACNAI1 were associated with SCZ.…”
Section: Discussionmentioning
confidence: 57%
“…Of note, a recent study also showed that genetic variants in CANCA1I were significantly associated with SCZ in Uighur Chinese population [ 30 ]. Six SNPs (rs132575, rs713860, rs738168, rs136805, rs5757760 and rs5750871) were found to be associated with SCZ in the study of Xu et al [ 30 ] We studied the linkage disequilibrium between these six SNPs and the SNP investigated in our study (i.e., rs4522708). We found that rs4522708 is linked with two previous reported SNPs (rs713860 and rs738168) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This animal model will facilitate further investigations of the role of Cav3.3 channels in impaired sleep spindle and nRT function in SCZ. Additional CACNA1I variants have been identified in SCZ patients, confirming CACNA1I as a genetic risk factor in SCZ [95,163,164]. CACNA1I is also considered a risk gene in autism [93] and other complex neuropsychiatric disorders [128].…”
Section: Cacna1i/cav33 In Neurological/psychiatric Diseasesmentioning
confidence: 89%